Comparative Analysis of Financial Reporting of Selected Small and Medium Enterprises (Smes) in Baguio City: Basis for a Financial Planning Model - CACLINI, MORAYA P. (The journal of contemporary issues in business and government, 2021)
This study aimed to determine the level of financial reporting compliance and comparative analysis of selected SMEs' financial statements to develop and propose a financial planning model as a tool for the financial decision-making of SMEs. Descriptive and correlational research was utilized. Mean, Standard Deviation, T-test, ANOVA, and Pearson Product Moment Correlation used for data analysis. The findings revealed that SMEs financial reporting compliance was not significantly different when grouped as to the length of existence, number of employees, asset capitalization, beginning liability, and position. The financial reporting compliance in terms of income, expense, asset, liabilities, equity, and earnings per share showed a significant relationship with financial statements analysis such as profit margin, dividends per share, inventory turnover, and total asset turnover of SMEs.